A reusable MOF supported single-site nickel-catalyzed direct N-alkylation of anilines with alcohols. (8th October 2022) - Lu, Yuanyuan; Chai, Huining; Yu, Kun; Huang, Chaonan; Li, Yujie; Wang, Jinyu; Ma, Jiping; Tan, Weiqiang; Zhang, Guangyao
Abstract: The direct N -alkylation of amines with alcohols is an efficient route through a borrowing hydrogen (BH) strategy. Herein, a highly selective, and reusable Ni(II)-bipyridine-based metal-organic framework (MOF) catalyst was designed for this organic transformation. This earth-abundant metal-based metal-organic framework (MOF) catalyst significantly outperform their homogeneous analogues and the immobilized catalyst was reusable for at least up to 4 cycles without significant decrease in the yield of the target product. Graphical abstract: Image 1 Highlights: A highly efficient and selective earth-abundant metal-based MOF catalyst has been prepared. The catalytic performance of Bpy-UiO-Ni is superior to its homogeneous counterpart in direct N -alkylation of amines. Efficient recyclability and high stability of the developed catalyst.